2021
DOI: 10.3390/biomedicines10010005
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acid Synthase Inhibitor Platensimycin Intervenes the Development of Nonalcoholic Fatty Liver Disease in a Mouse Model

Abstract: Non-alcoholic fatty liver disease (NAFLD) is a chronic liver disease affecting about 25% of world population, while there are still no approved targeted therapies. Although platensimycin (PTM) was first discovered to be a broad-spectrum antibiotic, it was also effective against type II diabetes in animal models due to its ability to inhibit both bacterial and mammalian fatty acid synthases (FASN). Herein, we report the pharmacological effect and potential mode of action of PTM against NAFLD in a Western diet/C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 36 publications
(62 reference statements)
1
4
0
Order By: Relevance
“…Data from the literature report that the expression of Cpt1a mRNA is up-regulated in CCl 4 -induced HF in mice and promote oxidative stress, while the silencing of Cpt1a (Cpt1a −/− mouse) protects against steatosis in CCl 4 -treated animals [60]. In agreement with this literature data [51,59,61] reported up-regulation of FASN genes in several hepatic fibrosis animal models, and our results indicate an up-regulation of Cpt1a and FASN genes. Both GLY and GLY-MN treatment restored FASN to levels comparable with untreated animals while, on the contrary, Cpt1a is strongly reduced only after GLY-MN, suggesting that the encapsulated drug contributed to a greater reduction in this gene, in line with the protective effect observed in the Cpt1 −/− mouse produced by Luo and co-workers [60].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Data from the literature report that the expression of Cpt1a mRNA is up-regulated in CCl 4 -induced HF in mice and promote oxidative stress, while the silencing of Cpt1a (Cpt1a −/− mouse) protects against steatosis in CCl 4 -treated animals [60]. In agreement with this literature data [51,59,61] reported up-regulation of FASN genes in several hepatic fibrosis animal models, and our results indicate an up-regulation of Cpt1a and FASN genes. Both GLY and GLY-MN treatment restored FASN to levels comparable with untreated animals while, on the contrary, Cpt1a is strongly reduced only after GLY-MN, suggesting that the encapsulated drug contributed to a greater reduction in this gene, in line with the protective effect observed in the Cpt1 −/− mouse produced by Luo and co-workers [60].…”
Section: Discussionsupporting
confidence: 91%
“…The TGF-β1 receptor has a crucial role in the development of the disease because it is involved in the activation of HSCs that are the major source of ECM in liver fibrosis and cirrhosis [17]. In addition, the TGF-β1 pathway impacts on lipid homeostasis in liver fibrosis [50][51][52]. However, the efficacy of GLY on the TGF-β1 pathway can be hindered by several factors which hamper the efficient delivery of drug due to blood dilution, immune system cleansing and loss in the gastrointestinal tract [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, some FASN inhibitors, such as platensimycin ( 38 ), have been shown to intervene in NAFLD progression in mouse models. Fortunately, some FASN inhibitors, such as TVB-2640 ( 32 ), a first-in-class and orally bioavailable FASN inhibitor, has undergone phase II clinical trials that have shown significant effects in reducing liver fat and improving biochemical, inflammatory, and fibrotic biomarkers after 12 weeks of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…FAS is constituted of two matching components (260–270 kDa), each harboring an acyl carrier protein (ACP) alongside six enzymatic centers, including acetyl/malonyl transferase (AMT), β-ketoacyl synthase (KS), β-ketoacyl reductase (KR), β-hydroxyacyl dehydratase (DH), enoyl reductase (ER), and thioesterase (TE) [ 15 ]. In instances of genetic obesity in rats and diabetes in humans, there is notable upregulation of FAS in adipose tissue [ 16 , 17 , 18 ]. Investigations have indicated that administering FAS inhibitors to mice resulted in decreased appetite and significant weight reduction.…”
Section: Introductionmentioning
confidence: 99%